2020
DOI: 10.1002/1873-3468.13731
|View full text |Cite
|
Sign up to set email alerts
|

Retargeting adenoviruses for therapeutic applications and vaccines

Abstract: Adenoviruses (Ads) are robust vectors for therapeutic applications and vaccines, but their use can be limited by differences in their in vitro and in vivo pharmacologies. This review emphasizes that there is not just one Ad, but a whole virome of diverse viruses that can be used as therapeutics. It discusses that true vector targeting involves not only retargeting viruses, but importantly also detargeting the viruses from off-target cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 309 publications
0
27
0
Order By: Relevance
“…The use of different capsid modifications can be advantageous to modulate viral clearance, uptake, or to reduce off-target transduction for gene therapy approaches. 37 The desired target cell specificity of HCAdV particles with genetic capsid modifications was introduced by exogenously added retargeting adapters 38 following amplification and purification of HCAdVs, again without the need to modify the original HCAdVs or HV vectors ( Figure 1 D). Retargeted HCAdV particles were additionally covered by a shield, formed by a trimerized scFv to prevent off-target infection and HCAdV clearance by neutralizing antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of different capsid modifications can be advantageous to modulate viral clearance, uptake, or to reduce off-target transduction for gene therapy approaches. 37 The desired target cell specificity of HCAdV particles with genetic capsid modifications was introduced by exogenously added retargeting adapters 38 following amplification and purification of HCAdVs, again without the need to modify the original HCAdVs or HV vectors ( Figure 1 D). Retargeted HCAdV particles were additionally covered by a shield, formed by a trimerized scFv to prevent off-target infection and HCAdV clearance by neutralizing antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…For gene therapy applications, the natural tropism of HAdV-C5 vectors for coxsackievirus and adenovirus receptor (CAR) has been ablated by genomic modifications to the adenovirus fiber knob. 37 The tropism of adenoviral vectors has been redirected to defined biomarkers using genetically encoded tags, or exogenously added adapter proteins. 37 , 38 While genetic modifications can lead to virion instability and low vector yields, 39 exogenously added adapters do not affect vector production and thus allow for versatile use of the vector in different cell types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain serotypes engage instead glycans and polysialic acids as primary attachment moieties [78,79]. The natural diversity of adenoviruses and their corresponding wide range of host-cell receptors is permitting; (i) constructing new vectors based on rare serotypes that can escape pre-exiting immunity to adenoviruses prevalent in the human population, for anti-cancer and vaccination purposes [80]; and (ii) changing the tropism of established vectors based on species C adenovirus serotype 5 into those of other serotypes so that cells with therapeutic relevance lacking CAR can be efficiently transduced [81]. For instance, genetic retargeting of vector particles through the exchange of the apical regions of the adenovirus serotype 5 fiber ( Figure 2) for those of species B adenovirus serotype 35 or 50 permits efficient transduction of CAR low /CD46 high hHSCs [82,83], human mesenchymal stromal cells (hMSCs) [84,85] and human muscle progenitor cells [86].…”
Section: A Brief Overview On the Biology Of Adenoviruses And Their Rementioning
confidence: 99%
“…Since a small portion of the Ad particles injected ip are able to enter the circulation, Ad vectors administered through this route are susceptible to clearance after interacting with blood components and residential macrophages in tissue and in the peritoneal cavity [83,139]. It was first shown that modifications of the fiber partially ablate neutralization of the virus [77,78,84,140], and later, that additional pseudotyping of the hexon or the ablation of FX binding sites in the hexon decreases liver sequestration, toxicity and vectorimmune system interactions in both ip and iv approaches [88,141,142]. Recently, Uusi-Kerttula et al combined triple detargeting through mutations on the fiber that block binding to CAR, the penton to block binding to αvβ3/5 integrins, and the hexon for FX binding, with insertion of the A20 peptide into the HI loop [143].…”
Section: Overcoming Physical Barriers To Dissemination Of Oncolytic Amentioning
confidence: 99%